13 The epidemiology of police-reported pedestrian injuries treated in North Carolina emergency departments: a focus on health disparities and serious injuries. (May 2020) - Harmon, Katherine; Peticolas, Katherine; Ising, Amy; Walleranna, Anne
Abstract : Statement of Purpose: Older adults, people of color, and residents of lower-income communities are disproportionately represented in pedestrian fatalities. Fatalities, however, represent a small proportion of all pedestrian traffic-related injuries. We linked crash, emergency department (ED) visit, and American Community Survey (ACS) data to examine the socio-demographic and crash characteristics of pedestrian injuries and their association with serious injuries in North Carolina (NC). Methods/Approach: We linked information for pedestrians from 2017 NC police-reported crashes to population-based ED visit and ACS data using hierarchical deterministic linkage methods. We used descriptive epidemiologic methods to calculate injury incidence rates and to examine the relationships among patient, socio-demographic, and crash characteristics and serious injuries, defined using an adapted definition of 'serious injury' developed by the National Transportation Safety Board. Results: We linked 45% percent of police-reported pedestrian injuries to NC ED visit data (N=1, 398). The 2017 rate of police-reported pedestrian injuries treated in NC EDs was 13.6 visits per 100, 000 person-years. Rates per 100, 000 person-years (in parentheses) were highest among adults 20–29 years of age (19.2), higher among men (15.5) than women (10.6), and higher among blacks (22.7) than whites (8.2). Patient and socio-demographic characteristics associated with serious injuries included age, sex, race/Hispanic ethnicity, expected source of payment, and county poverty level. Crash characteristics associated with serious injuries included posted speed limit, ambient light, number of lanes, and striking vehicle type. Conclusion: Pedestrian injuries are not distributed evenly across the NC population. Communities of color and counties with high levels of poverty are disproportionately impacted. Key crash characteristics are associated with rates of serious injury. Significance/Contribution to Injury and Violence Prevention Science: Policies, interventions, and other countermeasures designed to prevent pedestrian injuries should recognize and address social disparities and promote health equity.